2013
DOI: 10.1063/1.4824761
|View full text |Cite|
|
Sign up to set email alerts
|

Extraordinarily large perpendicular magnetic anisotropy in epitaxially strained cobalt-ferrite CoxFe3−xO4(001) (x = 0.75, 1.0) thin films

Abstract: Perpendicular magnetic anisotropy (PMA) of cobalt-ferrite CoxFe3-xO4 (x = 0.75 and 1.0) epitaxial thin films grown on MgO (001) by a reactive magnetron sputtering technique was investigated. The saturation magnetization was found to be 430 emu/cm3 for x = 0.75, which is comparable to that of bulk CoFe2O4 (425 emu/cm3). Torque measurements afforded PMA constants of Kueff=9.0 Merg/cm3 (Ku=10.0 Merg/cm3) and Kueff=9.7 Merg/cm3 for x = 0.75 and 1.0, respectively. The value of Kueff extrapolated using Miyajima's pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 22 publications
3
51
1
Order By: Relevance
“…Recently, we found that CFO lms grown on MgO(001) substrates by reactive sputtering exhibit large saturation magnetization comparable to the bulk and extremely high uniaxial magnetic anisotropy of 13 Merg/cm 3 along the normal to the lm Co 0.75 Fe 2.25 O 4 (001) 6) . The composition ratio of Fe and Co is also a crucial parameter 18) .…”
Section: Cobalt Ferrite Lmmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we found that CFO lms grown on MgO(001) substrates by reactive sputtering exhibit large saturation magnetization comparable to the bulk and extremely high uniaxial magnetic anisotropy of 13 Merg/cm 3 along the normal to the lm Co 0.75 Fe 2.25 O 4 (001) 6) . The composition ratio of Fe and Co is also a crucial parameter 18) .…”
Section: Cobalt Ferrite Lmmentioning
confidence: 99%
“…Recently, we have found that high quality epitaxial lms of these spinel ferrites can be grown by reactive magnetron sputtering techniques and that epitaxial distortion causes the ferrite lm to exhibit high magnetic anisotropy. 6) In this paper, we present an overview of the developed lm growth technique based on a reactive sputtering method and the magnetic and structural properties of the as-grown epitaxial thin lms magnetite, maghemite, and cobalt-ferrite. In the following section, the experimental procedures for growing spinel ferrite lms are described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among many ferromagnetic oxides, cobalt ferrite (CFO) shows a significantly large magnetoelastic effect. 17,18 The easy axis can be varied between the out-of-plane and in-plane directions by changing the lattice distortion if CFO is in a film form. A previous report revealed that epitaxial CFO on MgO (001) shows a large perpendicular magnetic anisotropy of K u of over 1 MJ/m 3 under a tensile strain.…”
mentioning
confidence: 99%
“…The effective uniaxial magnetic anisotropy constant K u evaluated by magneto-torque measurements at RT, was K u ∼ 1 MJ/m 3 and -5.2 MJ/m 3 for CFO/MgO and CFO/MAO, respectively. 17,24 Those values of K u were extracted from the high-field torque data using Miyajima's analysis. 25 We note that the easy axis is defined as perpendicular to the film; therefore, a positive value of K u means a perpendicular magnetization film.…”
mentioning
confidence: 99%